2022
DOI: 10.1002/jcp.30707
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of adrenergic mechanisms for the stress‐induced breast cancer carcinogenesis

Abstract: Breast cancer is the most common and deadliest type of cancer in women. Stress exposure has been associated with carcinogenesis and the stress released neurotransmitters, noradrenaline and adrenaline, and their cognate receptors, can participate in the carcinogenesis process, either by regulating tumor microenvironment or by promoting systemic changes. This work intends to provide an overview of the research done in this area and try to unravel the role of adrenergic ligands in the context of breast carcinogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 173 publications
(462 reference statements)
0
4
0
Order By: Relevance
“…Adrenergic stress is one of several culprits behind immunosuppression inside the TME, and has evolved recently as an important regulator of inflammation, immunity, and cancer [ 96 ]. Chronic release of NA inside the TME influences tumor growth by impeding immune responses, as is evident in preclinical models of some cancers [ 10 , 97 ]. β2-AR, among adrenergic receptors, is the most studied receptor for its immunosuppressive function in T lymphocytes.…”
Section: Perspective For Car-t Cell Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Adrenergic stress is one of several culprits behind immunosuppression inside the TME, and has evolved recently as an important regulator of inflammation, immunity, and cancer [ 96 ]. Chronic release of NA inside the TME influences tumor growth by impeding immune responses, as is evident in preclinical models of some cancers [ 10 , 97 ]. β2-AR, among adrenergic receptors, is the most studied receptor for its immunosuppressive function in T lymphocytes.…”
Section: Perspective For Car-t Cell Therapymentioning
confidence: 99%
“…β2-Adrenergic receptors can modulate the functions of various immune cells as the corresponding receptors are displayed on the surface of T cells, natural killer (NK) cells, and dendritic cells (DCs) [ 7 , 8 ]. The ligand for β2-AR is released inside the tumor microenvironment (TME) and leads to inhibitory signaling in T lymphocytes [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adrenergic signaling may promote neoplastic transformation of breast epithelial cells in the initiation phase; however, it may also favor the metastatic potential of breast cancer cells during cancer progression. Although the presence of mesenchymal cells is essential for the induction of tumorigenesis, adrenergic signaling not only affects directly mesenchymal and tumor cells but also the function and activity of other cell types in the TME, where macrophages, fibroblasts, and fat cells can take on a kind of protumor phenotype [ 34 ]. Based on a previous BRCA cell line study, amongst all AR types, ß2ARs seem to be the most relevant receptors involved in the development of BRCA metastasis.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In an orthotopic ovarian cancer mouse model it has been demonstrated that depletion of TAMs by using clodronate liposomes attenuated tumor growth through the inhibition of angiogenesis [ 75 ]. Moreover, TAMs also secrete other proangiogenic growth factors such as EGF, PDGF, FGF2, TGF-β, TNF-α, semaphorin 4D, adrenomedullin, thymidine phosphorylase, IL-6, IL-1 β , IL-8, CCL2, CXCL8, and CXCL12 which promote neovascularization at several steps including supporting the proliferation of endothelial cells (eCs), as well as inducing sprouting, tube formation, and maturation of new blood vessels [ 4 , 11 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. In addition, there are several enzymes that are often expressed by TAMs including MMP-2, MMP-7, MMP-9, MMP-12, and cyclooxygenase-2 that can have a profound influence on tumor angiogenesis [ 83 ].…”
Section: Pro-tumorigenic Roles Of Tamsmentioning
confidence: 99%